Implementasi Strategi Guru dalam Meningkatkan Minat Belajar Anak di KB Alam Aisyiyah Bojonegoro - Novi Dyah Ayu Putri; Desi Ismawati; Puspita Dewi Rarasati (Early Childhood Journal, 2026)
This study aims to determine the teacher's strategy in increasing the learning interest of children at KB Alam Aisyiyah Bojonegoro. This study was conducted with a qualitative approach with a case study research type. This study was conducted from May to June with a total of 17 students who were in Class Ali 5 at KB Alam Aisyiyah Bojonegoro School. Data were obtained through observation, interviews, and documentation. Data analysis techniques used data reduction, data presentation, and conclusion drawing. Data validation techniques in this study used triangulation techniques and source triangulation. The results of the study show that teachers at KB Alam Aisyiyah Bojonegoro in increasing children's learning interest use several strategies including (1) game-based learning strategies (2) learning strategies through singing, (3) media-based learning strategies, in this case every day teachers always use interesting media by using concrete objects to help the learning process, (4) project-based learning strategies. These four strategies really made children enthusiastic and interested in participating in each lesson. This demonstrates that using learning strategies can increase children's interest in learning.